An exploration of an educational kit on dance movement therapy techniques to be used by parents and family members of children ages 6-11 diagnosed with autism spectrum disorder to improve to improve social communication - Chan, Cassandra Colleen B.; Reyes, Mitzi Marie Aguilar (Quezon City College of Fine Arts, University of the Philippines Diliman, 2017)
"Behavior is communication. Change the environment and behaviors will change." -Dr. Lana David. Communication is what makes the world go round. It helps us understand, connect and sympathise with other people. Most people use speech and non-verbal communication to interact with others. To most, engaging in meaningful conversation comes naturally. For example, a young child learns from his environment and his parents that one cannot scream in a room full of people. Unfortunately, not everybody has the ability to behave in such a way. Individuals with autism spectrum disorder have a hard time dealing with seemingly obvious social cues. Cognitively, majority exhibit difficulty in meaningful communication. Such behaviours are: inability to keep focus, sensitivity to loud noises and sounds, inability to keep eye contact, impaired acquisition of speech, inability to understand facial expressions and social cues, difficulty in learning and limited movement. The Heart at Play Foundation, whom of which offers dance movement therapy sessions to those with special needs, have parents who bring their children with autism to the sessions to help them to develop both cognitively and physically. Unfortunately, it takes a longer time for these kids to benefit from the program due to their condition. For some kids, it takes at least 3-5 years to see the change in behaviour. This issue on frequency of classes and learning retention can be seen as an issue and opportunity to tackle. It is through study that the researcher will be able integrate The Heart ay Play exercises, dance movement therapy exercises and visual communication to provide these parents and alternative supplementary materials in the form of a home therapy kit.
Thesis (Bachelor of Fine Arts in Visual Communication)--University of the Philippines Diliman
Bibliography : leaves 217-219.
Keywords: Dance therapy for children; Autism spectrum disorders in children; Autism in children